Isolation and Characterization of α-Amylase Enzyme on Brown Planthopper (Nilaparvata lugens Stal) On Rice - Syakuro, Muhammad Yusuf Abdan; Haryadi, Nanang; Muhlison, Wildan; Sucipto, Irwanto (The Journal of Experimental Life Science, 2022)
Brown leafhopper (Nilaparvata lugens Stal) is an important pest in Indonesia that causes heavy losses. The rice was damaged by N. Lugens sucking plant liquid in the form of carbohydrates in the form of starch. Environmentally friendly control methods are needed to reduce the increasingly high use of inorganic pesticides. Control of N. lugens with biotechnology can be done by inhibiting the metabolic cycle in these insects. This method utilizes the proteins available in rice seeds to stop the performance of enzyme α-amylase in the digestive system of N. lugens. α-amylase is an enzyme that plays a role in the process of starch degradation so that it becomes a simpler form both in microorganisms. The characterization of α-amylase enzymes in insects is an important first step to the determination of appropriate protein inhibitors so that they can be used to produce pest-resistant Genetically Modified Organisms crops. The research was conducted in the Agrotechnology laboratory, University of Jember. The research began with isolation and purification of α enzymes from brown stems and then continued with testing of α-amylase activity. Test parameters include the effect of temperature, pH, and substrate concentration on the activity of the α-amylase enzyme. The results showed that supernatant extracted from brown planthoppers produces a clear zone in the agar medium, which means the activity of enzymes α-amylase in the hydrolysis of starch. The pH value of 6 provides the most optimum conditions for the activity of α enzymes. The α-amylase enzyme is able to work optimally in the temperature range of 30°C - 45°C, and experiences a decrease in activity when the temperature reaches 50°C. The α-amylase enzyme shows the ability to hydrolyze the amylase substrate to a concentration of 0.8 μg.μL-1. Keywords: α-amylase, Nilaparvata lugens Stal, Rice.